Complete Genome Sequences of Two Streptococcus suis Strains Isolated from Asymptomatic Pigs - Minowa-Nozawa, Atsuko (Microbiol Resour Announc, 2020)
Streptococcus suis is an important zoonotic pathogen that causes major economic problems in the pig industry worldwide and serious infections in humans, including meningitis and septicemia. Here, we report the complete genome sequences of two strains isolated from asymptomatic pigs.